Dynamic analysis of harvesting and handling systems for biomass energy feedstocks - Mantovani, Bárbara Heliodora Machado; Peart, Robert M.; Gibson, Harry (Pesquisa Agropecuaria Brasileira, 2014)
A SLAM II combination network discrete event model was developed to simulate harvest and transport of corn residue, hay and wood chips for continuous delivery to a biomass conversion plant. The model used ten years of climatological and production data of the state of Indiana, USA, in order to quantify the effect of weather on the system, analysed in many situations. Weather played an important role on system performance, especially on collection and transportation of corn residue and hay. There were situations when it was better not to buy forestry equipment, but to rent it, in order to decrease production costs. Corn residue yields averaged 3.3 t/ha and hay yields averaged 1.9 t/ha. Wood chips produced 86 t/ha for clear cut, 53 t/ha for thinning and 40 t/ha for plantations (100, 20 and 5 years rotation age respectively). On an average weather year it cost up to 71% more to collect and transport corn residue bales than wood chips from clear cut. Stacks and bales cost about the same to produce, but it cost 55% more to transport bales. Production and transportation costs were about twice as much for clear cut compared to plantation.